Vitamin D level and telogen hair loss: A Case control study - Turkan, Taiceer A.; Al-Rawi, Jamal R. (Journal of the Faculty of Medicine Baghdad, 2021)
Abstract Background: Hair loss is a common skin condition. Hair is not a vital organ but losing it has a worse effect on the psychological state of the patient and may interrupt his daily social activities. Telogen effluvium founded to be the commonest noninflammatory cause to diffuse hair loss. Since nutritional disturbances are one of the triggering factors for it. It might be useful in the management of TE Due to the limited number of studies& little information is available on this subject possible role of vitamin D or its deficiency should be studied further. Aim of the study: to determine the association between Telogen effluvium and vitamin D level. Materials and methods: This is a case-control study performed in a period between December 2018 until June 2020; in Baghdad dermatology center at medical city. One hundred women who were seeking treatment for diffuse hair shedding and who hadn’t received treatment or supplements yet and One hundred fifty control subjects are chosen from patients who were referred to the dermatology clinic for the treatment of nevi and who are not pregnant or lactating, had no systemic or local scalp diseases are included in the study. Full History, physical examination performed for all cases including looking for cutaneous diseases, supplements & drug intake. Serum Vitamin D3 is measured using (Ichroma (TM), Boditech Med Inc., Korea). Result: A total of 250 females were included in this study, 100 of them got telogen effluvium & 150 were patients who attend dermatology clinic seeking treatments for nevi or skin tag (control group) .The mean age of cases was (22.59 ±4.837 year) that wasn’t significantly different from mean age of control group (23.647±6.022 years) (p-value =0.127). The mean level of Vitamin D was significantly lower than that of control group (11.16±4.49) Vs (18.98±10.65), P value <0.001. Vitamin D mean level in acute phase was significantly higher than that of chronic phase pts. (11.68±4.77 & 9.93 ±3.55 respectively), p value=0.04. Mean vit. D among symptomatic patients. (9.7 ± 3.5) was significantly lower than that among asymptomatic pts. (13±4.19) (p=0.001).No significant association were noticed between job & residence of the patients of both groups, (P-value =0.283 & 0.069 respectively (. Conclusion: Age mean difference was not significant among cases and controls. Deficiency in vitamin D may assume a possible leading cause of telogen effluvium among women with hair loss. Cases were significantly associated with low level of Vitamin D3 than controls.Low level of vitamin D was dominant among housewives, urban women, and among symptomatic patients with acute duration.